Relationship Of Characteristics With Work Fatigue In Oil Palm Harvesters In Afdeling V Ptpn Ii Palm Sebrang - manalu, gadis; Harahap, Reni Agustina (Journal for Quality in Public Health, 2023)
Fatigue is a condition that can be experienced by workers, usually the fatigue is characterized by the weakening of the muscles in the workforce so that workers are unable to do their work again. The research aims to determine relationship of characteristics with work fatigue in oil palm harvesters in Afdeling V PTPN II Sawit Seberang in 2023. This is a quantitative research with a "cross sectional" approach by taking samples using total sampling of 36 respondents. The research results showed that 15 respondents (41.7%) had work fatigue, while 21 people (58.3%) did not experience fatigue. Variables associated with fatigue are nutritional status (p-value 0.03), working period (p-value 0.04),length of sleep (p-value 0.028), cigarette consumption (p-value 0.004). Suggestions in this study are that oil palm harvesters are expected to maintain a healthy body at work by utilizing rest periods such as stretching muscles, adequate intake of nutrients and mineral water and complying with instructions for the use of personal protective equipment for occupational safety and health.